Power system stability enhancement using flux control for excitation system - Goldoost-Soloot, R.; Mishra, Y.; Ledwich, G.; Ghosh, Arindam; Palmer, E. (Institute of Electrical and Electronics Engineers ( IEEE ), 2013)
This paper proposes a new controller for the excitation system to improve rotor angle stability. The proposed controller uses energy function to predict desired flux for the generator to achieve improved first swing stability and enhanced system damping. The controller is designed through predicting the desired value of flux for the future step of the system and then obtaining appropriate supplementary control input for the excitation system. The simulations are performed on Single-Machine-Infinite-Bus system and the results verify the efficiency of the controller. The proposed method facilitates the excitation system with a feasible and reliable controller for severe disturbances.